Performance assessment of a novel design of double slope solar: Energy and water quality analysis - Sabir Widatalla; Hassan Mohammed; I.B. Sapaev; Ramachandran T; John William Grimaldo Guerrero; Aman Shankhyan; P Vijaya Kumar; Vikasdeep Singh Mann; Hossein Sharif (Energy Exploration & Exploitation)
The ability to treat saltwater to make it suitable for human consumption has long been sought by mankind. More than three-quarters of the earth's surface is covered with saltwater. Although this water is important for some forms of transportation and fishing, it contains too much salt to sustain human life or agricultural activities. One way to desalinate water is to use solar energy-based technologies. One of these technologies is the use of a solar device to evaporate and condense water, along with the generation of electricity through a transparent photovoltaic panel, providing freshwater. The current work focused on developing a simple solar still with low-cost materials that can be built by anyone, anywhere. In addition, the study presented three-dimensional multiphase CFD models for a single-slope solar still. Computational modeling using ANSYS 15 enables precise simulation and optimization of this integrated solar system, maximizing its overall efficiency and output. This dual-purpose solar energy utilization offers a pathway to provide both clean water and electricity to communities in remote or resource-constrained regions, thereby enhancing their quality of life and promoting sustainable practices. Simulation results indicate that increasing the saline water temperature from 60°C to 70°C results in a 67% increase in water production at a wind speed of 3 m/s. A further increase in temperature from 80°C to 90°C leads to a 141% increase in water production under the same wind conditions.